Coaching biomechanics interface: simulation modelling - Hiley, M. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Computer simulation modelling is a powerful tool that can be used to gain insight into the mechanics of gymnastics technique. Having identified the underlying mechanics performance may be optimised and new skills developed. As computer processing power has increased so have the applications for simulation modelling. Research is currently being conducted to combine simulation models with virtual reality environments to produce innovative gymnastics training aids.